Switching costs and the extent of potential competition in Brazilian banking - Mariana O. Silva; Claudio R. Lucinda (EconomiA, 2017)
Switching costs are a leading cause of customer lock-in in banking, reducing the extent of competition and increasing market power in this industry. This paper tries to estimate these costs using a methodology that does not require customer microdata. The estimates obtained here—using bank accounting information collected on a quarterly basis from 2009 to 2011—indicate substantial switching costs in the deposit market, and such costs tend to be lower for customers of larger banks. Additionally, there is some evidence that much of a bank's market share is due to its continued relationships with customers over time (a lock-in effect). Thus, the extent of potential competition in Brazilian banking could be severely limited by these costs. – – Custos de mudança s\~ao uma das principais causas de retenç\~ao de clientes na indústria bancária, reduzindo a competiç\~ao e aumentando o poder de mercado nesta indústria. Este artigo tenta mensurar tais custos usando uma metodologia que n\~ao necessita o uso de microdados. As estimativas obtidas aqui - utilizando informaç\~oes contábeis dos bancos em uma base trimestral entre 2009 e 2011 - indicam custos de mudança substanciais no mercado de depósitos à vista, e tais custos tendem a ser menores para clientes de bancos maiores. Além disso, existe alguma evidência que a maior parte da participaç\~ao de mercado de um banco é devido às suas relaç\~oes com os consumidores ao longo do tempo (efeito lock-in). Portanto, a extens\~ao da competiç\~ao potencial na indústria bancária brasileira pode ser fortemente limitada por tais custos.
Keywords: L13; G21; 330; Switching costs; Banking; Industrial organization